Approximate expressions for BER performance in downlink mmWave MU-MIMO hybrid systems with different data detection approaches - Ortega, Alvaro Javier; Sampaio-Neto, Raimundo; David, Rodrigo Pereira (IET communications, 2020)
Millimetre-wave (mmWave) communications have been regarded as a key technology for the next-generation cellular systems since the huge available bandwidth can potentially provide the rates of multiple gigabits per second. Conventional precoding and combining techniques are impractical at mmWave scenarios due to manufacturing costs and power consumption. Hybrid alternatives have been considered as a promising technology to provide a compromise between hardware complexity and system performance. This study examines, using a semi-analytic approach, the downlink performance of massive MU-MIMO mmWave systems in terms of the bit error rate (BER). Also, a general expression is derived to estimate an upper bound/approximation to the BER performance via the Monte Carlo method, which can be used for any hybrid precoder/combiner, modulation and different data detectors. Numerical results evidence that the approximate BER expressions provide values very close to the ones obtained through simulation using only two statistical moments related to parameters of the system, mean and variance.